2012
DOI: 10.1590/s0102-67202012000300004
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida do paciente submetido à cirurgia videolaparoscópica para tratamento para doença do refluxo gastroesofágico

Abstract: -Background -Gastroesophageal reflux disease is a chronic disease of high prevalence in Western countries, with negative effects on quality of life. Surgery is indicated for patients with intolerance to continuous medication, prolonged treatment or control, or in complicated forms of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
1
0
1
Order By: Relevance
“…Symptom persistence requires endoscopic dilation or even a new surgery, with resulting total remission. Andrade et al (2012) 2 analyzed the quality of life of 43 patients submitted to surgical GERD treatment and reported that 58.1% were very satisfied and 37.2% were satisfied with the result.…”
Section: Methodsmentioning
confidence: 99%
“…Symptom persistence requires endoscopic dilation or even a new surgery, with resulting total remission. Andrade et al (2012) 2 analyzed the quality of life of 43 patients submitted to surgical GERD treatment and reported that 58.1% were very satisfied and 37.2% were satisfied with the result.…”
Section: Methodsmentioning
confidence: 99%
“…Todas as medidas terapêuticas buscam melhorar a função motora do esôfago, aumentar a pressão do esfíncter esofágico inferior, assim como reduzir o prejuízo causado pela acidez gástrica, neutralizando-a ou mesmo suprimindo--a, contudo, como já mencionado, o maior empecilho no tratamento é manter os pacientes assintomáticos, visto que mesmo após o tratamento cirúrgico feito através de laparoscopia, ainda há queixas reincidentes de disfagia, dificuldade para eructar, flatulência e diarreia (KLAUS et al, 2003;PEREI-RA, et al, 2007;ANDRADE et al, 2012).…”
Section: Discusãounclassified